POLITIK DAN KAUM FEMINIS - Audra Jovani (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2011)
AbstractFeminist theory attempted to analyze the various conditions that shape the lives of womenand explore diverse cultural understanding about women. Feminist theory was originallydirected to the political objective of the Woman Movement. The feminist rejected the viewthat the inequality between men and women are naturally. Thinking as a feminist involvesattempts to challenge many of the things that are considered as â€œknowledgeâ€. Historically,live in a society dominated by men, women are more often made into objects rather than thecreator of knowledge. As the result, many things are passed down as an objective knowledgeabout the world is actually produced by men (white skin, middle class and heterogeneous).Women are in a variety of different positions in local and global contexts and displayeddifferently in art, literature and other media; the different in terms of nationality, ethnicity,education, language, class, family, work, ability or disability and sexuality is crucial.Keywords: Politics, Feminism, Feminist